2021
DOI: 10.1111/jdv.17588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical determinants of complete response to vismodegib in locally advanced basal cell carcinoma: a multicentre experience

Abstract: Of the enrolled subjects, 71% were women and 29% were men. Based on POEM 18% had mild, 50% moderate and 22% severe AD. Based on the EASI score 42% were classified as mild, 27% as moderate and 7% as severe. Three per cent had clear skin, and 20% had almost clear skin based on EASI score. (Table 1).Thornton et al. 3 showed that the cost per retained participant in 24 studies recruited through Facebook was between $1.36 and $110. The costs in our study were in the higher end probably due to the geographic limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
5
2
Order By: Relevance
“…However, the proportion of CR was superior in our series (47.4%) than that reported in clinical trials (32%) [6,14,15]. Similarly, other retrospective and real-world studies have shown better ORR results when compared with clinical trials [10][11][12][13]16]. This discrepancy may be due to different standards in evaluation and specially to the reliance on clinical examination instead of others like imaging by the dermatologist in real-life settings.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…However, the proportion of CR was superior in our series (47.4%) than that reported in clinical trials (32%) [6,14,15]. Similarly, other retrospective and real-world studies have shown better ORR results when compared with clinical trials [10][11][12][13]16]. This discrepancy may be due to different standards in evaluation and specially to the reliance on clinical examination instead of others like imaging by the dermatologist in real-life settings.…”
Section: Discussioncontrasting
confidence: 71%
“…Recently, several groups have addressed the effectiveness, safety, and utilization of vismodegib in clinical routine [9][10][11][12][13]. Herms et al [9] specifically studied the follow-up of patients with complete remission of laBCC after vismodegib discontinuation in a group of 116 patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infiltrative type BCC was the most frequent histopathological subtype, accounting for 34.8% of all aBCC diagnoses. The high prevalence of this histopathological subtype has been reported also in pivotal trials and real-life studies on aBCC [7, 911, 18], where a similar association between high-risk histology and decreased tumor response has been described [19]. Occurrence of >2 AEs was also significantly associated with a higher probability of nonresponse to HHI.…”
Section: Discussionmentioning
confidence: 57%
“…Patients experiencing multiple AEs might undergo dose reduction or treatment discontinuation, which may affect tumor response outcomes. To this regard, some authors reported an association between intermittent dosing and nonresponse to HHI [18,20], while others claimed an unchanged efficacy profile [21][22][23].…”
Section: Discussionmentioning
confidence: 99%